Determination of the Radon Progeny Activity Size Distribution in Laboratory Conditions - Eliska Fialova; Petr P. S. Otahal (Atmosphere)
Knowledge of the active size distribution of radon daughters is one of the main parameters for determining the effective dose from inhalation of short-term radon decay products. However, this parameter is crucial for accurately determining an effective dose; there are currently very limited possibilities for determining it. This paper describes the laboratory validation of a method for determining the activity size distribution of radon decay products using the Dekati ELPI+ cascade impactor and the Graded Screen Array Diffusion Battery (GSA DB). Using nuclear track detectors placed on individual impaction plates of the cascade impactor, the equivalent equilibrium activity concentration of individual size classes can be determined in the range from 17 nm to 10 μm. A diffusion battery was used to detect smaller particles in the unattached fraction area. The presented method can further refine the knowledge of the activity size distribution of radon decay products in different types of workplace atmospheres. Workplaces with higher radon concentrations differ significantly in the size distribution of aerosol particles, radon activity concentration, and equilibrium equivalent activity concentration.